Analysis of Students’ Satisfaction and Service Quality Gap for Private Universities of Bangladesh - MM Ismail Hossin; Rafikul Islam; Dolhadi Zainudin (Journal of Islamic Management Studies, 2022)
The primary objective of this study is to identify gaps between students’ expectations and the level of satisfaction with the services that they receive from the private universities of Bangladesh. Three hundred eighteen students from various private universities in Bangladesh took part in an online survey. From the responses, it is found that a wide range of gaps exists between students’ expectations and their level of satisfaction with the service quality items. Therefore, the university administration needs to take adequate measures to bridge the gaps as much as possible. This research contributes to the existing body of knowledge in the field of higher education, as well as provides insight to private universities in Bangladesh to produce skilled and well-rounded graduates. The findings will help Bangladeshi private universities produce graduates who can contribute to improving productivity and economic growth in Bangladesh.